Морфологічна мінливість Veronica arguteserrata Regel & Schmalh. – нового адвентивного виду на Дніпропетровщині - Лісовець, Олена Іванівна; Lisovets, Оlena; Кушнірова, Юлія Віталіївна; Kushnirova, Yulia (Дніпровський національний університет імені Олеся Гончара, 2020)
Досліджено фенотипну мінливість Veronica arguteserrata Regel & Schmalh. – нового адвентивного виду азіатського походження з родини Подорожникових (Plantaginaceae Juss.) в умовах Дніпропетровщини. Вид є ефемером: рослини починають вегетувати в другій половині квітня, цвітуть у середині травня, плодоносять у кінці цього ж місяця, у червні жовтіють і відмирають. У досліджених фітоценозах зі збільшенням щільності популяції Veronica arguteserrata спостерігається тенденція до зменшення показників висоти рослин, довжини другого міжвузля, довжини і ширини листової пластинки, кількості квітконосів і квіток, довжини і ширини приквітників, довжини квітконіжки, діаметра віночка і до збільшення довжини першого міжвузля, ширини і довжини коробочки. Найбільша варіабельність виявилася характерною для таких ознак вегетативної сфери: довжини кореня, довжини листкової пластинки; генеративної сфери: кількості квіток і плодів на рослині. Саме ці ознаки вносять найбільшу частку в морфологічну мінливість дослідженого виду й обумовлюють її загальну фенотипну пластичність. У результаті дисперсійного аналізу статистично доведено вплив показника щільності популяції на морфометричні ознаки рослин. Найбільший вплив щільність популяції має на такі ознаки вегетативної сфери: довжину першого міжвузля і довжину листкової пластинки; генеративної сфери: на діаметр віночка і довжину приквітників. Таким чином, мінливість саме цих ознак можна розглядати як механізм внутрішньопопуляційних морфологічних пристосувань нового адвентивних виду Veronica arguteserrata в умовах Дніпропетровщини. In the Dnipro area, Veronica arguteserrata is a new adventitious species of Asian origin from the family Plantaginaceae Juss., growing in the same ecological conditions – in shaded areas with moderate anthropogenic impact due to trampling, on loose soils and on parchment plots. The species is ephemeral: begins to grow in the second half of April, blooms in mid-May, bears fruit at the end of the same month, turns yellow in June and dies. We used 160 plants to study the morphological and ecological variability of Veronica arguteserrata. For analysis, we measured plant height, root length, length of the first and second internodes, length and width of leaf blade, number of peduncles, number of flowers, width and length of bract, corolla diameter, length and width of the fruits, number of seeds in the nest and number of fruits on the plant. The average values of all components were determined, the errors and population density, the number of individuals per 0.01 m2 were determined. Using a grid of 20 × 10 cm, divided into eight squares 5 × 5 cm, calculated the density of plants in tenfold repetition. The accuracy of density estimation, calculated as the ratio of error of the arithmetic mean to the arithmetic mean and expressed as a percentage, was 3.8–6.3%. The accuracy of assessment of other traits ranged from 2.2 to 7.5%, which is quite acceptable for field research. Analysis of the data showed that Veronica arguteserrata in the study area forms a fairly dense density of grasses, in which almost no other species are immersed. With increasing density, there is a tendency to increase the length of the first internode and reduce the area of the leaf blade, the number of peduncles, flowers and fruits on individuals. Within the parks, the plants were mowed at the end of the growing season. Probably due to mowing, as well as a slightly greater impact of trampling, the density of park populations is lower than on the highway near buildings. Synecological analysis showed that in the conditions of Dnipro area Veronica arguteserrata is a xeromesophyte, mesotroph, sciogeliophyte and ruderant. In the studied phytocenoses with increasing population of Veronica arguteserrata there is a tendency to decrease plant height, length of the second internode, length and width of the leaf blade, number of peduncles and flowers, length and width of bracts, peduncle length, corolla diameter and corolla diameter increase and box length. The highest variability was observed in the following signs from the vegetative sphere of Veronica arguteserrata plants: root length, leaf blade length, in the generative sphere: the number of flowers and of fruit on the plant. It is these features that make the largest share in the morphological variability of the studied species and determine its overall ecological and morphological plasticity. As a result of analysis of variance, the influence of population density on morphometric characteristics of plants was statistically proved. The population density has the greatest influence on the following features of the vegetative sphere: the length of the first internode and the length of the leaf blade; in the generative sphere: the diameter of the corolla and the length of the bract. Thus, the variability of these traits can be considered as a mechanism of intra-population morphological adaptations of the new adventitious species Veronica arguteserrata in the Dnipro area. The new adventitious species needs further monitoring studies to assess the level of impact on the ecosystems of Dnipro area.
Morphological variability of Veronica arguteserrata Regel & Schmalh. – new adventive species in Dnipro area
Keywords: адвентивний вид; adventive species; Veronica arguteserrata; Veronica arguteserrata; морфологічна мінливість; morphological variability; щільність популяції; population density